PHYSICOCHEMICAL ANALYSIS FOR QUALITY DETERMINANT OF NATURAL BAR SOAP WITH BINAHONG LEAF EXTRACT AND LEMONGRASS ESSENTIAL OIL - Karimatulhajj, Hanifah; Rohmansyah, Ryan (Universitas Muhammadiyah Magelang, 2025)
There are two kinds of coconut oil in market that could be a natural soap base, filtered and unfiltered coconut oil that made the differences in fatty acid levels. In the previous study, the unfiltered coconut oil has the higher fatty acid than filtered coconut oil. It might could decrease pH level in the bar soap. It could appear caused by the excess of free fatty acid in the soap that not react with the lye and peroxidation may occur than made the rancid smell in the bar soap during the storage. In addition, the use of herbal component like plant extract and essential oil would contribute to pH level and water content of the soap that could affect the soap quality. Both parameters must be evaluated to determine the bar soap quality. This study used herbal extract of binahong leaf and sereh wangi essential oil. There was divided to the four groups: formula 1 using filtered coconut oil and herbal extract, formula 2 using unfiltered coconut oil with herbal extract, formula 3 using filtered coconut oil without herbal extract, and formula 4 using non filtered coconut oil. The quality of the natural soap was evaluated for organoleptic, the pH level, moisture content, and the TLC Profile of the bar soap solution. All formulas were evaluated and all of them had green and white porcelain colour, hard soap, a pH between 9-10 on day 38, moisture content up to 15,5%, so from SNI 2021 the soap had a good quality.